Restore me - Mafi, Tahereh (New York : Harper, 2018)
"It's been sixteen days since Juliette Ferrars killed the supreme commander of North America and took over as ruler of the Reestablishment on the continent ... Juliette thought she'd won. She took over sector 45 and now has Warner by her side. But she's still the girl with the ability to kill with a single touch--and with so much power in her young hands, the world is watching her every move, waiting to see what happens next."--Jacket.
Keywords: Dictatorship -- Juvenile fiction; Government, Resistance to -- Juvenile fiction; Soldiers -- Juvenile fiction; Ability -- Juvenile fiction; Young adult fiction; Ability -- Fiction; Soldiers -- Fiction; Dictatorship -- Fiction; Love -- Fiction; Science fiction; LOVE -- Fiction; Young adult fiction; Dictatorship -- Fiction; Soldiers -- Fiction; Government, Resistance to -- Fiction; YOUNG ADULT FICTION -- Dystopian; YOUNG ADULT FICTION -- Romance -- Paranormal; YOUNG ADULT FICTION -- Science Fiction; Dictatorship; Government, Resistance to; Dictatorship -- Juvenile fiction; Resistance to government -- Juvenile fiction; Soldiers -- Juvenile fiction; Ability -- Juvenile fiction; Dictatorship -- Fiction; Resistance to government -- Fiction; Soldiers -- Fiction; Ability -- Fiction; Science fiction; Science fiction